Stakeholders' Perceptions of Inclusive Education Policy: A Sociological Review of Government Strategies and Efforts in Achieving Equitable Education Services - Irmawati; Rita Rahmawati; Rusliandy; Irma Purnamasari; Novel Anak Lyndon (Universitas Djuanda Bogor, 2026)
This study aimed to analyze the role of local government and stakeholder perceptions of inclusive education policies from a sociological perspective. This study used qualitative research methods, including observation, interviews, literature reviews, and FGDs. The research informants were local government employees responsible for education, school principals, teachers, and parents of students. The sample comprised 20 informants, selected purposively. Data analysis was conducted through thematic analysis. The study's results indicated three main themes: readiness to implement inclusive education policies, stakeholder perceptions, and government efforts to realize equitable education. Inclusive education policies have been implemented, but not optimally, especially regarding schools' readiness to implement them. From the perspective of stakeholder perceptions of inclusive education, there was a good understanding, which has an impact on the emergence of solidarity and stakeholder participation in supporting the implementation of inclusive education policies. Government efforts have been made to assist schools in implementing inclusive education. However, the budget policy for inclusive schools has not been institutionalized. In addition to successful implementation, some factors that could strengthen policy implementation but have not been fully addressed include local cultural characteristics that have not been incorporated into inclusive education policies. Recognizing these cultural factors is crucial for fostering equitable education and ensuring policies resonate with local communities.